Effect of Hydration Forms and Polymer Grades on Theophylline Controlled-Release Tablet: An Assessment and Evaluation - Molham Sakkal; Mosab Arafat; Priya Yuvaraju; Rami Beiram; Labeeb Ali; Mohammednoor Altarawneh; Abdul Razack Hajamohideen; Salahdein AbuRuz (MDPI AG, 2024)
Background: Drug release from controlled release delivery systems is influenced by various factors, including the polymer's grade and the drug's hydration form. This study aimed to investigate the impact of these factors on the controlled release of theophylline (THN). This research compares the monohydrate form found in branded products with the anhydrous form in generic equivalents, each formulated with different polymer grades. Methods: Quality control assessment was conducted alongside in vitro evaluation, complemented by various analytical techniques such as X-ray diffraction (XRD) and scanning electron microscopy (SEM). Additionally, thermal analyses using differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA) were employed. Results: Quality control assessments demonstrated that the generic tablets exhibited lower average weight and resistance force compared to the branded ones. In vitro tests revealed that generic tablets released contents within 120 min, compared to 720 min for the branded counterpart. Characterization using XRD and SEM identified disparities in crystallinity and particle distribution between the three samples. Additionally, the thermal analysis indicated consistent endothermic peaks across all samples, albeit with minor variations in heat flow and decomposition temperatures between the two products. Conclusions: This study demonstrated that variations in polymer grade and hydration form significantly impact THN release.